2019
DOI: 10.1101/619619
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pupil-associated states modulate excitability but not stimulus selectivity in primary auditory cortex

Abstract: 1 2 Recent research in mice indicates that luminance-independent fluctuations in pupil size predict 3 variability in spontaneous and evoked activity of single neurons in auditory and visual cortex. These 4 findings suggest that pupil is an indicator of large-scale changes in arousal state that affect sensory 5 processing. However, it is not known whether pupil-related state also influences the selectivity of 6 auditory neurons. We recorded pupil size and single-unit spiking activity in the primary auditory c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…While raw pupil size has been successfully employed as a marker for internal arousal processes in sensory circuits (Augustinaite & Kuhn, 2020;Liang et al, 2020;Lin et al, 2019;McGinley et al, 2015a;Molnár et al, 2021;Petty et al, 2021;Schröder et al, 2020;Schwartz et al, 2020), other studies, including ours, have instead considered the pupil size signal as a continuous oscillatory process and focused on its dynamics (Reimer et al, 2014(Reimer et al, , 2016. We further extended this perspective by exploiting a decomposition method that respects the non-stationary, multi-scale nature of the pupil size signal (Huang et al, 1998), and found that several timescales were related to dLGN firing modes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While raw pupil size has been successfully employed as a marker for internal arousal processes in sensory circuits (Augustinaite & Kuhn, 2020;Liang et al, 2020;Lin et al, 2019;McGinley et al, 2015a;Molnár et al, 2021;Petty et al, 2021;Schröder et al, 2020;Schwartz et al, 2020), other studies, including ours, have instead considered the pupil size signal as a continuous oscillatory process and focused on its dynamics (Reimer et al, 2014(Reimer et al, , 2016. We further extended this perspective by exploiting a decomposition method that respects the non-stationary, multi-scale nature of the pupil size signal (Huang et al, 1998), and found that several timescales were related to dLGN firing modes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore future work will need to establish if other thalamic nuclei, or neuronal sub-types within the dLGN (Kerschensteiner & Guido, 2017;Piscopo et al, 2013;Rosón et al, 2019), are similarly modulated by pupil size dynamics. Finally, although the pupil size signal is often lauded as an index for internal modulations that occur in the absence of other overt behaviors, considering pupil size in the context of other behaviors such as locomotion (Reimer et al, 2014;Vinck et al, 2015) or eye movements (Schwartz et al, 2020) promises to reveal a more diverse coupling to neural measures. Indeed, expanding the notion of behavioral state to a high-dimensional set of latent behaviors has been successful in predicting neural activity, especially in thalamic neurons (Stringer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation